Beyond the Black and White TV : Asian and Latin American spectacle in Cold War America - Han, Benjamin M. (Rutgers University Press, 2020)
"This is the first book that examines how "ethnic spectacle" in the form of Asian and Latin American bodies played a significant role in the cultural Cold War at three historic junctures: the Korean War in 1950, the Cuban Revolution in 1959, and the statehood of Hawaii in 1959. As a means to strengthen U.S. internationalism and in an effort to combat the growing influence of communism, television variety shows, such as The Xavier Cugat Show, The Ed Sullivan Show, and The Chevy Show, were envisioned as early forms of global television. Beyond the Black and White TV examines the intimate moments of cultural interactions between the white hosts and the ethnic guests to illustrate U.S. aspirations for global power through the medium of television. These depictions of racial harmony aimed to shape a new perception of the United States as an exemplary nation of democracy, equality, and globalism"--